2022
DOI: 10.3390/jrfm15060237
|View full text |Cite
|
Sign up to set email alerts
|

The ESG Disclosure and the Financial Performance of Norwegian Listed Firms

Abstract: The world is constantly changing, and with an evolving global environmental crisis, there is a growing trend of Corporate Social Responsibility, and Environmental, Social, and Governance (ESG) disclosure initiatives. The final report on the new E.U. taxonomy for sustainable activities was released in 2020, making ESG disclosure more relevant. This paper investigates the effects of ESG initiatives on the financial performance of Norwegian listed companies from 2010 to 2019. ESG is measured through the Thomson R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 69 publications
7
65
0
4
Order By: Relevance
“…It is observed from the results that the companies which have high compliance with sustainability disclosure conditions tend to have more market performance. Hence, the results align with larger global findings (Giannopoulos et al, 2022; Lee et al, 2009).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It is observed from the results that the companies which have high compliance with sustainability disclosure conditions tend to have more market performance. Hence, the results align with larger global findings (Giannopoulos et al, 2022; Lee et al, 2009).…”
Section: Resultssupporting
confidence: 88%
“…Further, the ESG disclosure scores have a positive and statistically significant impact on accounting (ROA) and market performance (Tobin's Q). Giannopoulos et al (2022) suggest that ROA could reduce as companies commit greater resources towards ESG disclosure practices, which suggests some of the earlier studies connoting a negative association between the two variables. Followed by Barnett (2007) argued that shareholders willing to invest in a socially responsible company may accept the lower returns resulting from resource reallocation.…”
Section: Resultsmentioning
confidence: 96%
“…The relationship between economic growth and environmental degradation has garnered much attention from researchers due to the adverse impacts of carbon dioxide emissions on climate change and global warming (Albitar et al 2021 , 2022 ; Alkaraan et al 2023 ; Elmarzouky et al 2021 ; Giannopoulos et al 2022 ; Karim et al 2021 ; Moussa et al 2022 ; Sharif et al 2020 ). Despite the numerous studies that have examined the causal link between economic activity and environmental quality, the empirical evidence remains mixed (Mohamed Abdul Ghani et al 2017 ; Radmehr et al 2021 ).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Giannopoulos et al (2022) examined the effects of the ESG initiative on the financial performance of Norwegian listed companies. ESG was measured through Thomson Reuters Eikon and financial performance was measured through return on assets (ROA) and Tobin’s Q.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Shalhoob and Hussainey (2023) found that SMEs in Saudi Arabia lack awareness of ESG practices and disclosures and, therefore, the extent of their importance to sustainability performance. Giannopoulos et al (2022) examined the effects of the ESG initiative on the financial performance of Norwegian listed companies. ESG was measured through Thomson Reuters Eikon and financial performance was measured through return on assets (ROA) and Tobin's Q.…”
Section: Introductionmentioning
confidence: 99%